STYLISTIC SPEECH ANALYSIS OF DR. H. SUSILO BAMBANG YUDHOYONO, THE PRESIDENT OF INDONESIA, CASE: The India and Indonesia Business Forum - Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2011)
This paper presents a stylistic speech of Indonesian President, Dr. H. Susilo Bambang Yudhoyono. It is to find out how the President’s speech addresses the honour to the Associated Chambers of Commerce and Industry of India which has a forum of business community in terms of theme, plot structure, stylistic and linguistics categories .The theme expressing the remarkable prospect of strategic partnership between Indonesia and India through bilateral economic cooperation. There are thirteen main sectors that are highlighted in the speech. The words in general are intended to highlight and show how he felt about Indonesia that can cooperate with India in setting up the World Economic Forum’s third country in business Forum. The president’s speech repeated use of illocutionary act of assertive and commissives convinces his audience and fellow citizens that the condition of Indonesia and India enhance cooperation in Business. Also, it is found the use of passive sentences. The cohesion in speech is achieved by the use of cohesive devices such as co-reference pronouns and conjunctions throughout the speech, the President himself as a respectful citizen and addresses his audience as his inseparable colleagues in the use of the pronoun “we” and the possessive pronoun “our”. To better activate his audience’s interest more compound and complex sentences are used. The figures of speech used are metaphor, and very few in the forms of personification and anaphora. Key words: stylistic, theme, plot structure, linguistics categories, illocutionary, co-reference